Factors Influencing Maternal Mortality in The Bangka Belitung Archipelago - Hastuti; Kamalia Layal (Sriwijaya Journal of Medicine, 2026)
Maternal mortality remains a key indicator of health system performance. Although Indonesia has seen a general decline in maternal mortality rates, they remain high, with notable fluctuations observed in the Bangka Belitung Islands, particularly an upward trend following the COVID-19 pandemic peak in 2021. This study aimed to identify factors associated with maternal mortality in the province. A case-control design was employed using secondary data from 2023, including Maternal Verbal Autopsy reports, medical records from the Maternal Perinatal Death Notification (MPDN) system, and maternal cohort data from local health centers. A total of 117 subjects were included, comprising 39 cases and 78 controls. Two variables were found to significantly influence maternal mortality in the Bangka Belitung Islands Province in 2023: parity (p = 0.020; OR = 0.306; 95% CI: 0.113–0.831) and antenatal care visits (p < 0.001; OR = 23.233; 95% CI: 7.266–74.226). Of these, antenatal care visits were identified as the most dominant predictor. These findings underscore the urgent need to strengthen maternal healthcare services in line with clinical standards, particularly ensuring comprehensive and timely antenatal care. Improving service governance may enhance early detection of high-risk pregnancies, facilitate safer deliveries, and ultimately reduce maternal mortality in the Bangka Belitung Islands.